Avaliação Representada: Um Instrumento De Discriminação - Elaine Teresinha Dias Dal Mas (EccoS – Revista Científica)
The objective of this work is to introduce a representation of the scholar evaluation under the untemporality dominium of the ideas originated in history and its vicissitudes, showing as reference the Benjaminian mosaicist thinking. Analyzing the psychologizing and normative influence of the psychological theories originated in Health Science and its prejudicial, stereotyped and stigmatizing diffusion.